Effect of compression garments on short-term recovery of repeated sprint and 3-km running performance in Rugby Union players - Hamlin, M. J.; Mitchell, C. J.; Ward, F. D.; Draper, N.; Shearman, J. P.; Kimber, N. E. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to investigate whether wearing compression garments during recovery improved subsequent repeated sprint and 3-km run performance. In a randomized single-blind crossover study, 22 well-trained male rugby union players (mean ± SD: age 20.1 ± 2.1 years, body mass 88.4 ± 8.8 kg) were given a full-leg length compressive garment (76% Meryl Elastane, 24% Lycra) or a similar-looking noncompressive placebo garment (92% Polyamide, 8% Lycra) to wear continuously for 24 hours after performing a series of circuits developed to simulate a rugby game. After the 24-hour recovery, garments were removed and a 40-m repeated sprint test (10 sprints at 30-second intervals), followed 10 minutes later by a 3-km run, was completed. One week later, the groups were reversed and testing repeated. Relative to the placebo, wearing the compressive garment decreased time to complete the 3 km by 2.0% ± 1.9% (mean ± 90% confidence interval). Additionally, average sprint times improved (1.2% ± 1.5%) and fatigue was diminished (-15.8% ± 26.1%) during the repeated sprint test in the compression group compared with the placebo group. Delayed onset muscle soreness was substantially lower in the compression group compared with the placebo group, 48 hours after testing. Wearing compressive garments during recovery is likely to be worthwhile, and very unlikely to be harmful for well-trained rugby union players.